2015
DOI: 10.1242/jeb.119453
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of left ventricle cardiomyocyte ultrastructure across development in the kangaroo Macropus fuliginosus

Abstract: The heart and left ventricle of the marsupial western grey kangaroo Macropus fuliginosus exhibit biphasic allometric growth, whereby a negative shift in the trajectory of cardiac growth occurs at pouch exit. In this study, we used transmission electron microscopy to examine the scaling of left ventricle cardiomyocyte ultrastructure across development in the western grey kangaroo over a 190-fold body mass range (0.355−67.5 kg). The volume-density (%) of myofibrils, mitochondria, sarcoplasmic reticuli and T-tubu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Smaller western grey kangaroos also have hearts that are relatively larger for their body mass than do larger kangaroos (Snelling et al. ,b). Relatively larger hearts (for aerobic capacity) and relatively greater ankle torques (for acceleration and hopping speed) of smaller kangaroos may reflect their greater predation risk (Dawson, ).…”
Section: Discussionmentioning
confidence: 99%
“…Smaller western grey kangaroos also have hearts that are relatively larger for their body mass than do larger kangaroos (Snelling et al. ,b). Relatively larger hearts (for aerobic capacity) and relatively greater ankle torques (for acceleration and hopping speed) of smaller kangaroos may reflect their greater predation risk (Dawson, ).…”
Section: Discussionmentioning
confidence: 99%
“…Protein content per-MC and MC median volumes were scaled to animal growth using the regression line between log-log covariates with the equation y = bx α for ontogenic allometry 15 where y is the trait being scaled, x is the growth determinant, and b (intercept) & α (slope) are constants. The animal age is replaced as the growth determinant by body mass and time is cancelled out in the derivative 14,19,20 . Cell growth and protein accumulation are the traits of interest.…”
Section: Brief Methodsmentioning
confidence: 99%
“…Snelling et al (2015b) found that heart mass of grey kangaroo joeys grows hyperallometrically while the joeys are in the pouch, as they approach attaining endothermy and leaving the pouch. Associated changes at the cellular level in the heart also occur within the joey, with increases in mitochondria volume and muscle contractile machinery associated with leaving the pouch and obtaining endothermy (Snelling et al, 2015a). Through day 42 post-hatching in the chicken, ventricle size increases through both hyperplasia and hypertrophy after hatching (Li et al, 1997).…”
Section: Morphological Changes Associated With Endothermymentioning
confidence: 99%